Relevance of Mental Health Care for Drivers to Make them Competitive - Nelly Dioses Lescano; Humberto Iván Morales Huamán; David González Espino (Revista Finlay, 2024)
Foundation: taking care of the mental health of vehicle drivers is essential for them to be competitive and to prevent traffic accidents because one of the causes of accidents is the poor mental health of drivers. Objective: determine the relevance of mental health care for vehicle drivers to avoid accidents and to make them competitive. Methods: the sample was 219 drivers and collectors of land transportation in Trujillo, La Libertad, Peru; who answered the General Well-being Test-5, previously applied in Peru by other researchers, made up of 5 composite questions. The null (Ho) and alternate (Ha) hypothesis test; were raised with a respect to the decisive score of 54.75 points. Results: for questions 2 and 4, the alternative hypothesis was approved with the indication that mental health care for drivers is pertinent so that they can be relaxed; also so that they rest well and start the day feeling well rested. For questions 1, 3 and 5, the null hypothesis was accepted. Conclusions: it is perceived that the lowest averages correspond to questions 2 and 4, then mental health care is pertinent for public transport drivers, so that they can receive psychological assistance to feel relaxed and rested. For the other questions, the null hypothesis is accepted.